Bioequivalence of Rivaroxaban Hard Capsules vs. Film-Coated Tablets in Healthy White Volunteers - Agnieszka Gierczak-Pachulska; Michał Kaza; Katarzyna Jarus-Dziedzic; Olga Czerepow-Bielik; Agnieszka Segiet-Święcicka; Grzegorz Huszcza; Katarzyna Sidoruk; Daniel Rabczenko; Piotr J. Rudzki (Polskie Towarzystwo Farmaceutyczne, 2024)
Rivaroxaban is an oral anticoagulant that is a selective, direct factor Xa inhibitor. It is used to prevent thrombotic events of atherosclerotic etiology and to prevent stroke and peripheral embolism in adult patients with nonvalvular atrial fibrillation. The aim of studies was to assess the bioequivalence of two orally administered products: test (Zarixa hard capsules) vs. reference (Xarelto® film-coated tablets). Two crossover, 2-period, randomized, open-label, laboratory-blinded studies were conducted in healthy White male and female volunteers. A single oral dose (Study 1: 10 mg fasting, Study 2: 20 mg fed) of the test or reference product was followed by a minimum 7-day washout. Blood was collected up to 48 h after administration. Plasma concentrations of rivaroxaban were measured using a validated LC-MS/MS method. The bioequivalence criteria for 90% confidence intervals (CI) of the log-transformed geometric mean ratios (test/reference) for the two primary pharmacokinetic parameters (AUC(0-t) and Cmax) were set at 80.00-125.00%. Vital signs, laboratory parameters, and adverse events were monitored. 34 of 36 volunteers completed Study 1, and geometric mean ratios were 97.96% (90% CI 93.69-102.42%) for AUC(0-t), and 89.35% (90% CI 84.28-94.72%) for Cmax. All 36 volunteers completed Study 2, and geometric mean ratios were 103.57% (90% CI 98.75-108.63%) for AUC(0-t), and 95.17% (90% CI 87.35-103.70%) for Cmax. All of 90% CIs for the primary pharmacokinetic parameter ratios met acceptance criteria. There were no serious adverse events. Results of both studies indicate that the test product (Zarixa) is bioequivalent to the reference product (Xarelto®). Both products were well tolerated.